Trend of the incidence and mortality rate of lip cancer in Central Serbia from 1999-2014 - Ignjatović Aleksandra M.; Stojanović Miodrag M.; Milošević Zoran G.; Anđelković-Apostolović Marija R.; Stojković Branislava B.; Topalović Marija M.; Otašević Suzana A. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Background: Lip cancer is the most frequent oral cancer. The aim of this study was to present and estimate trends in the incidence and mortality of lip cancer in Central Serbia during a 16-year period, from 1999 to 2014. Material and methods: This registry-based study was carried out based on the data extracted from publicly available Yearbooks of the Institute of Public Health of Serbia - Incidence and Mortality in Central Serbia, from 1999 to 2014. The trend and the annual percentage change (APC) of the incidence and mortality rate with the corresponding 95% confidence intervals were calculated by performing join point regression analyses. Results: A total number of 1,922 cases (1,402 in men and 520 in women) of lip cancer were registered in Central Serbia from 1999 to 2014. The crude rate (CR) and age-standardized rate (ASR-W) of the incidence in males decreased (p=0.001, p<0.001, respectively) during the study period with APC of 4.3%, 5.2%, respectively. In females, CR and ASR-W of incidence showed the only significant trend between 2003-2014, 2006-2014, respectively with APC 12.3, 24.3%, respectively. ASR-W of mortality rate in males showed the decreasing trend with APC 4.5%. Conclusions: Our results reveal that the incidence of lip cancer declines trough the study period. The mortality rate is low and stable.